Phenotype definition is a main point in genome-wide association studies for bovine Mycobacterium avium ssp. paratuberculosis infection status. (27th May 2014) - Küpper, J.; Brandt, H.; Donat, K.; Erhardt, G.
<x content-type="archive" xml:space="preserve">Abstract</x> Paratuberculosis caused by Mycobacterium avium ssp. paratuberculosis (MAP) causes economic losses and is present in dairy herds worldwide. Different studies used different diagnostic tests to detect infection status and are the basis of genome-wide association (GWA) studies with inconsistent results. Therefore, the aim of this study was to identify and compare genomic regions associated with MAP susceptibility in the same cohort of cattle using different diagnostic tests. The GWA study was performed in German Holsteins within a case-control assay using 305 cows tested for MAP by fecal culture and additional with four different commercial ELISA-tests. Genotyping was performed with the Illumina Bovine SNP50 BeadChip. The results using fecal culture or ELISA test led to the identification of different genetic loci. Two single-nucleotide polymorphisms showed significant association with the ELISA-status. However, no significant association for MAP infection could be confirmed. Our results show that the definition of the MAP-phenotype has an important impact on the outcome of GWA studies for paratuberculosis.